3Rs awareness among UiTM Pulau Pinang students / Liza Tajul Aripin - Tajul Aripin, Liza (Faculty of Civil Engineering, Universiti Teknologi MARA, 2005)
Municipal solid waste (MSW) is considered one of the major environmental problems all over the world including Malaysia. Improper management of waste in our country is viewed as the main problems nowadays. It is because the effect of the unmanaged waste to the environment is very bad. Besides there are economic problems concerning the cost of solid waste management including cost of sorting, incineration and landfill. Another economic problem arises from Leaving MSW without proper management is loss of resources and energy. However, solving the problem is challenging because of lack of awareness of the problem. Therefore, the 3Rs (reducing, reusing and recycling) activity is one of the principles that were recognized as the best step to manage the waste in easiest way. Organization, individual, as well as students are the person that must involved in this program. Therefore, this study tries to explore the 3Rs awareness among the students of University Technology MARA Pulau Pinang in order to increase the level of awareness among them. The study is done by distribution of questionnaires among the respondents. It gauges the level of awareness among female students as well as the level of practice at campus. Besides, total weight of waste (recyclables and food waste) also determined in order to know the generation of waste at Kolej Baiduri and also the energy content of it. Overall, level of awareness, understanding and practice among respondents are high. The generation of waste also high as well as total energy content of it. Keywords – Municipal solid waste, solid waste management, reducing, reusing, recycling sorting, incineration, landfill, awareness, practice, energy content.